Empowering work-life balance: Exploring the nexus of flexible work arrangements, job satisfaction, and women's well-being in SMEs - Yen, Wendy Teoh Ming; Yen, Yuen Yee; Yen, Dan Yee (Asian Development Policy Review, 2024)
The aim of this study is to evaluate flexible working arrangements, work-life balance, and job satisfaction among women who work in small and medium enterprises (SMEs). The COVID-19 pandemic has highlighted the importance of flexible working arrangements, particularly for women juggling work and family responsibilities. The study evaluates the extent to which flexible working arrangements enable women to maintain a balance between work and family life in order to achieve work-related satisfaction. One hundred and thirty questionnaires were collected from the respondents for analysis. The analysis demonstrated a significant relationship between flexible working arrangements and work-life balance/job satisfaction among women working in SMEs. Importantly, work-life balance is an explicit factor that influences job satisfaction and mediates the relationship between flexible working arrangements and job satisfaction. These findings emphasize the need for organizations to seriously consider implementing flexible working arrangements and work-life balance policies in return for enhanced satisfaction of their workforce, especially women in SMEs in Malaysia. Research in this area is scarce; however, these findings offer valuable insights for SMEs in improving employee satisfaction and striving for growth and sustainability in the long run.